Peranan komunitas konser Kampung Jatitujuh dalam mempopulerkan seni budaya di Kabupaten Majalengka 1993-2016 (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2023)
The selection of the Komunitas Konser Kampung Jatitujuh as an object of research is based on an interest in cultural arts organizations that continue to preserve traditional arts in the midst of globalization, as well as their history background. The main problem in this essay is “How the role of Komunitas Konser Kampung Jatitujuh in Popularized Cultural Arts in Majalengka 1993-2016? Author use historical methods that consist of four steps which is heusristic, critic, interpretation and historiography. While the research technique is literature and field study in a way of interviewing some relevant resource person. The findings of this study are, the background of the establishment of Komunitas Konser Kampung Jatitujuh is the development of the Jatitujuh group of artists engaged in the development and preservation of cultural arts. The development of this organization underwent a change from an artist group called Musik Kampung to the Komunitas Konser Kampung Jatitujuh. The efforts of Komunitas Konser Kampung Jatitujuh in developing and preserving cultural arts in the form of work programs, socialization and collaboration with various parties. The influence of Komunitas Konser Kampung Jatitujuh on the aspects of the arts and culture of the community is the revitalization of traditional arts and culture, increasing public awareness of the development and preservation of cultural arts in the Jatitujuh.
Keywords: Globalitation; Kampung Jatitujuh; Preservation of cultural arts; Traditional arts